2019
DOI: 10.1186/s12913-019-4173-3
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes, perception and practices regarding antiretroviral therapy among HIV-infected adults in Antananarivo, Madagascar: a cross-sectional survey

Abstract: Background Adherence to antiretroviral therapy (ART) may be influenced by knowledge, perception and perception regarding ART. The purpose of this study was to assess knowledge, attitude/perception and practice regarding ART among people living with HIV/AIDS (PLHIV). Methods We conducted a cross-sectional survey to assess knowledge, attitudes, perception and practices ART in PLHIV. The survey was suggested to all PLHIV of at least 18 years old and who were on ART for at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 35 publications
9
10
0
Order By: Relevance
“…Some participants, however, stated that if one does not adhere strictly to the ART the viral load will increase and lead to early death. Similar findings have been made by Van Zyl et al (2017) and Raberahona et al (2019), whose responents indicated that taking ART is effective and will suppress HIV. On the contrary, Glendinning et al (2019) in a qualitative study to identify barriers to adherence to ART found that participants did not adhere to ART with the reason that the medicine could not cure and that they will still die from the disease and they believe that not doing well with HIV management is as a result of inadequate belief in God that does not guarantee to heal.…”
Section: R5supporting
confidence: 87%
See 2 more Smart Citations
“…Some participants, however, stated that if one does not adhere strictly to the ART the viral load will increase and lead to early death. Similar findings have been made by Van Zyl et al (2017) and Raberahona et al (2019), whose responents indicated that taking ART is effective and will suppress HIV. On the contrary, Glendinning et al (2019) in a qualitative study to identify barriers to adherence to ART found that participants did not adhere to ART with the reason that the medicine could not cure and that they will still die from the disease and they believe that not doing well with HIV management is as a result of inadequate belief in God that does not guarantee to heal.…”
Section: R5supporting
confidence: 87%
“…On the contrary, Glendinning et al (2019) in a qualitative study to identify barriers to adherence to ART found that participants did not adhere to ART with the reason that the medicine could not cure and that they will still die from the disease and they believe that not doing well with HIV management is as a result of inadequate belief in God that does not guarantee to heal. The participants of Raberahona et al (2019) further indicated that nonadherence or missing doses of ART will lead to the ineffectiveness of the medicine. Participants' belief in the positive and negative consequences of adherence and non‐adherence to ART respectively is a positive determinant for adherence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might be because disclosing one's own sero-status may enable the HIV-infected individual to get economic and social support from relatives; minimize HIV-related stigma which directly or indirectly encourages the patient to commence ART as early as possible and to adhere to the lifelong therapy and medical advice. 42,43 Likewise, individuals who attended educational level up to the level of college and above initiated ART earlier than those who could write and read only. Education enables people to understand the positive outcome of lifelong therapy; increases the selfconfidence to take decisions and change negative attitudes towards people living with HIV; educated people are more sociable, accept advice and direction that is provided by health providers as compared with those who are illiterate; 44,45 another study result reported that among HIVinfected individuals who initiated ART, 82.8% were literate while the rest were illiterate.…”
mentioning
confidence: 99%
“…This result contradict that of Raberahona et al where the perception level of the participant in their study was good. 20 The result of this study further revealed that more than half 159 (55.2%) of the respondents had negative perceived susceptibility, 200 (69.5%) had negative perceived benefits and 149 (51.6%) had negative perceived barrier. More than half of the respondents 160 (55.6%) had positive perceived severity 160 (55.6%) and 165 (57.3%) has positive perceived self-efficacy.…”
Section: Sub-optimal Adherencementioning
confidence: 63%